IMPLEMENTATION OF DIVERSITY AND INCLUSION PRINCIPLES IN UKRAINIAN TRAVEL BUSINESS - Rostovtsev, Serhii; Yariko, Myroslava (Індустрія туризму і гостинності в Центральній та Східній Європі, 2022)
The article considers the principles of implementing the diversity and inclusion approach in tourism organizations of Ukraine. Today, both Ukrainian businesspersons and researches mostly ignore this topic, although this issue is being studied quite seriously abroad. It is noted that this area has high prospects for the tourism business in the future, and will allow owners to gain additional benefits from the implementation of D&I principles. Along with the definitions of named concepts which are based on a sense of security, belonging and recognition, as well as opportunities for self-realization in the workplace, the article presents the benefits of D&I in the tourism business, characterizing this industry as one of the most attractive for this concept. In particular, it is noted that one of the advantages of following the principles of diversity in the organization is a significant increase in profitability of the company, which can be a major motivating factor for managers. In addition to the motives for implementation of the D&I concept in companies, the paper also states the main reasons for the low prevalence of this idea in Ukraine at the moment, among which are the lack of relevant knowledge and insufficient readiness of society to adopt such a concept. In order to introduce the principles of diversity and inclusion in tourism organizations of Ukraine, a number of recommendations are proposed for the creation of a culture of inclusion in the organization and the further implementation of D&I. At the same time, a particular attention is paid to key performance indicators, which will allow monitoring the level of implementation of these principles and identify problem areas in the company in order to further eliminate them. The results of the D&I principles implementation in a travel company can be: further involvement of qualified specialists and development of their skills, encouraging creativity and innovation by creating conditions in which employees with different views, diverse experience and education work effectively together, reduce of personnel turnover rate, and in general – attaining a competitive advantage in the market.